The use of Doppler vascular resistance in the early diagnosis of chronic kidney disease progression in patients with renal cell carcinoma - Serhiy Pasichnyk; Yulian Mytsyk; Lilia Hreschukh; P. Kowal; M. Pietrus; A. Borzhiievskyi; Оlexander Lychkovsky (Kazimierz Wielki University, 2022)
Development and progression of chronic kidney disease (CKD) in patients with renal cell carcinoma (RCC) after radical nephrectomy remains an extremely pressing contemporary issue. Postoperative changes of the ultrasound resistance index (RI) in the contralateral kidney not affected by the tumor after surgical treatment of RCC, as well as correlations between changes in IR and in glomerular filtration rate (GFR) remain far from being comprehensively investigated. The RI changes in the parenchyma of the intact (unaffected by the tumor) kidney before and after surgical treatment for RCC, and establishing correlations between RI changes and creatinine-dependent GFR remain unexplored issues. Objective. To assess the correlation between RI and GFR in the kidney not affected by the RCC before and after radical nephrectomy. Materials and methods. The study enrolled 49 patients. Group I included 37 patients with an initial diagnosis of RCC (on the right), Stage III of the disease, and without signs of chronic renal failure (GFR was ≥ 90 ml/min/1.73 m2). In patients with RCC, six months after surgery, the RI increase in the contralateral kidney unaffected by the tumor was significantly associated with a significant reduction in GFR. Thus, RI can be potentially used to predict the development of CKD in this patient population.